Infl uence of sustainable source of nutrient on growth and yield of sunfl ower (Helianthus annus L) - Umeed Ali Leghari, Ghullam Mustafa Leghari, Mehmooda Buriro, Shah Jahan Leghari*, (Journal of Plant Stress Physiology, 2015)
Sunflower is a one of the most important oilseed crop. Production of sunflower with the use of sustainable source of nutrient is cheap as compared with the application of synthetic fertilizers and its quality and soil heath improved by the application of organic chemical (OC) source of nutrient while chemical fertilizers are generally dangers for our environment and soil health. The nutrient requirement of sunflower can easily be carried by the self-made OC source of nutrient through this equation FYM + CaCO3 + H2 O + NO3 â†’ OC (OC source of nutrient) with very low cost, so a farmer can self-made and fulfill nutrient requirement of crop and can obtain higher yield. A field experiment was carried out during 2013 at village Mir Khan Leghari near Agriculture Training Institute Sakrand, district Nawabshah (Sindh). The sunflower variety HO-1 was sown by using randomized complete block design with tree replications. Three levels of self-made OC source of nutrient viz: T1 = 200 kg/ha, T2 = 300 kg/ha, and T3 = 500 kg/ha was used. Regarding to the result maximum plant height, stem girth, number of leaves, head diameter, seed yield (140 cm, 7.60 cm, 16/plant, 15.70 cm, 1580.00 kg/ha, respectively) were recorded in T3 in which high dose (500 kg/ha) of self-made OC source of nutrient were applied. While the minimum plant height 110 cm, stem girth 3.25 cm, leaves per plant 12, head diameter 9.50 cm, seed yield 1300.40 kg/ha were recorded in T1 plot, where low dose (200 kg/ha) of self-made OC source of nutrient were applied in this plot.